Recent advancements in gene therapy for sickle cell disease and β-thalassemia - Li, Lushen; Mandal, Pankaj K. (Frontiers in Hematology, 2024)
β-hemoglobinopathies, including sickle cell disease (SCD) and β-thalassemia, are prevalent monogenic disorders causing abnormal hemoglobin structure or production that affect millions globally. Current available therapies for SCD and β-thalassemia are primarily symptomatic treatments and allogeneic hematopoietic stem cell transplant (HSCT). Allo-HSCT is the only curative treatment, which has limitations. Gene therapy using genetically modified hematopoietic stem cells (HSCs) holds promise to be an effective curative therapy. Recently approved ex vivo genetically modified HSC-based therapeutics (CASGEVY, LYFGENIA, ZYNTEGLO) have shown remarkable and durable therapeutic benefits for SCD and β-Thalassemia. In this review article, we discuss the current genetic approaches and innovative strategies to ensure safe and effective gene therapy for SCD and β-thalassemia and summarize findings from completed and ongoing clinical trials. We also discuss prospects and challenges of in vivo gene editing with CRISPR/Cas technology for SCD and beta-thalassemia that may simplify manufacturing and treatment process. In vivo gene therapy may minimize the risks associated with ex vivo gene therapy and may overcome multiple barriers associated with complex gene therapy products for wider patient access, especially in developing regions of the world where these diseases are highly prevalent.